A systematic review and meta-analysis of the association between vitamin A intake, serum vitamin A, and risk of liver cancer. Issue 2 (June 2018) - Leelakanok, Nattawut; D'Cunha, Ronilda R.; Sutamtewagul, Grerk; Schweizer, Marin L.
Background: Previous evidence supports that vitamin A decreases the risk of several types of cancer. However, the association between vitamin A and liver cancer is inconclusive. Aim: This systematic review and meta-analysis summarizes the existing literature, discussing the association between vitamin A intake, serum vitamin A, and liver cancer in adult populations. Methods: A systematic literature review was performed by searching the EMBASE, PubMed, Scopus and International Pharmaceutical Abstract databases using terms related to vitamin A (e.g. retinol, α-carotene, β-carotene, and β-cryptoxanthin) and hepatic cancer without applying any time restriction. A meta-analysis was performed using random effect models. Results: The meta-analysis of five studies showed no association between serum retinol and liver cancer (pooled risk ratio = 1.90 (0.40–9.02); n = 5 studies, I 2 = 92%). In addition, the systematic review of studies from 1955 to July 2017 found studies that indicated no association between the intake and serum level of α-carotene ( n = 2) and β-cryptoxanthin ( n = 1) and the risk of liver cancer. Further, the associations between retinol intake ( n = 3), β-carotene intake ( n = 3), or serum β-carotene ( n = 3) and liver cancer were inconclusive. Conclusions: Current information on the association between vitamin A intake and liver cancer or serum vitamin A and liver cancer are limited. Most studies demonstrated no association between dietary vitamin A and the risk of liver cancer. However, the finding was based on a small number of studies with potential publication bias. Therefore, large observational studies should be conducted to confirm these associations.